Characterisation of a Novel Producer, the Antimicrobial Properties and the Molecular Target of Zelkovamycin - Tarantini, Francesco Saverio (2020)
The rise of antimicrobial resistance poses a threat to the treatment of infections caused by pathogenic and opportunistic bacteria, including Staphylococcus aureus and Pseudomonas aeruginosa.